The Contribution of Inspirational Leadership Practices of Academic Leaders to Achieve Organizational Excellence at King Abdulaziz University (The International Journal for Scientific Research, 2025)
The study aimed to know the degree of practicing inspirational leadership and the level of organizational excellence among academic leaders, in addition to knowing the degree of contribution of inspirational leadership practices among academic leaders in achieving organizational excellence at King Abdulaziz University, and to reveal statistically significant differences in the average response of the study sample members regarding the degree of practicing inspirational leadership and the level of organizational excellence among academic leaders attributed to each of (gender, academic rank, years of experience), and to achieve the study objective, the descriptive correlational approach was used, as the study community consisted of all faculty members at King Abdulaziz University, numbering (3669) members, and a simple random sample consisting of (356) members was selected. The results showed that the degree of practicing inspirational leadership among academic leaders was (agree) with an arithmetic mean of (4.10), and that the level of organizational excellence among academic leaders was (agree) with an arithmetic mean of (4.06), and that the degree of contribution of inspirational leadership practices among academic leaders in achieving organizational excellence was (0.827), i.e. (83%). It was found that there were no statistically significant differences in the response of the study sample members regarding the degree of practicing inspirational leadership attributable to the variable (gender, academic rank, years of experience), and no statistically significant differences in the response of the study sample members regarding the level of organizational excellence attributable to the variable (gender, years of experience), and no statistically significant differences in the response of the study sample members regarding the level of exploitative excellence attributable to the variable (academic rank), in contrast to the presence of statistically significant differences in the response of the study sample members regarding the level of exploratory excellence and structural excellence attributable to the variable (Academic rank) in favor of the rank of (Professor). In light of the study's results, the researcher makes a set of recommendations, the most important of which is the need for leaders to adopt inspirational leadership practices due to their direct positive impact on organizational excellence in universities.
Keywords: Inspirational Leadership; Organizational Dexterity